Comparing Common Themes in Wine Poetry Between Khayyam and Abu Hindi (Journal of Human Sciences, 2024)
Wine poetry has held significant importance for poets and researchers since ancient times, gaining prominence in cultures such as the Arabic culture, where the poet Abu Hindi was the first to describe wine in Islam, and the Persian culture, where the poet Omar Khayyam became one of the most prominent poets of wine poetry. These two poets share a set of themes that reveal their leniency towards Islamic jurisprudence. Using a descriptive analytical approach, this article attempts to illustrate the common themes in the wine poetry of Abu Hindi and Khayyam in his quatrains and compare them, to highlight the differences in their presentation styles. The study concludes that Khayyam utilized his philosophy to convey his ideas, presenting reasons and logical arguments, and benefiting from religious intertextuality, whereas Abu Hindi's style was simple and clear, and other results that we will present in our paper, which aims to clarify the intentions of ancient poets in resorting to wine, and what wine required of the poet's departure from the norm, the importance of the research lies in the fact that it is the first study that aims to comparison between these two poets, and the first that studies those themes in both of them poets.